High figure-of-merit p-type transparent conductor, Cu alloyed ZnS via radio frequency magnetron sputtering. (23rd November 2017) - Maurya, Sandeep Kumar; Liu, Ya; Xu, Xiaojie; Woods-Robinson, Rachel; Das, Chandan; Ager, Joel W; Balasubramaniam, K R
Abstract: p -type transparent conducting Cu alloyed ZnS thin films from Cu x Zn 1 − x S targets ( x = 0.1, 0.2, 0.3, 0.4, and 0.5) were deposited on glass substrates via radio frequency sputtering. x-ray diffraction and TEM–SAED analysis show that all the films have sphalerite ZnS as the majority crystalline phase. In addition, films with 30% and 40% Cu show the presence of increasing amounts of crystalline Cu2 S phase. Conductivity values  ⩾400 S c m − 1 were obtained for the films having 30% and 40% Cu, with the maximum conductivity of 752 S c m − 1 obtained for the film with 40% Cu. Temperature dependent electrical transport measurements indicate metallic as well as degenerate hole conductivity in the deposited films. The reflection-corrected transmittance of this Cu alloyed ZnS (40% Cu) film was determined to be  ⩾75% at 550 nm. The transparent conductor figure of merit ( Φ T C ) of the Cu alloyed ZnS (40% Cu), calculated with the average value of transmittance between 1.5 to 2.5 eV, was  ≈276 μ S .